Economic Analysis of the Preliminary Design of a Chemical Mini-Plant to Produce Palm Oil Based Estolide Calcium Sulfo-Ole Heavy -duty Bio grease with a Capacity of 36 Tons/Year - Luthfi, Muhammad; Sukirno, Sukirno (Diponegoro University, 2025)
The rapid growth of the automotive, manufacturing, and heavy-duty industries has increased lubricant demand, particularly lithium-based grease. However, due to supply constraints and rising costs, calcium is a more sustainable substitute for lithium in lubricants. This study develops heavy-duty bio grease based on palm oil estolide with calcium sulfo-oleate as a more economical and eco-friendlier alternative. The research adopts a pilot-scale approach with a 36 tons/year production capacity, aligned with Micro, Small, and Medium Enterprises (MSMEs). The product, heavy-duty bio grease Calcium Sulfo-Ole, uses Estolide Base Oil SAE 40 as the primary component. The process includes epoxidation, esterification, saponification, and formulation. Testing confirms that the ester-based oil has high viscosity and oxidative stability, making it suitable for NLGI 2 standard applications in heavy machinery. Economic analysis indicates strong viability, with a positive Net Present Value (NPV) of Rp1.3 billion over 10 years, Internal Rate of Return (IRR) of 13%, and Return on Investment (ROI) of 206%. The Break-Even Point (BEP) reached 83% capacity, proving feasibility. This bio grease reduces reliance on lithium-based lubricants while promoting sustainable, plant-based lubricants.